Effects of sleep fragmentation on glucose metabolism in normal subjects - Stamatakis, Katherine A; Punjabi, Naresh M (Chest, 2010)
Sleep disorders are increasingly associated with insulin resistance, glucose intolerance, and type 2 diabetes mellitus. Whether the metabolic toll imposed by sleep-related disorders is caused by poor-quality sleep or due to other confounding factors is not known. The objective of this study was to examine whether experimental sleep fragmentation across all sleep stages would alter glucose metabolism, adrenocortical function, and sympathovagal balance. Sleep was experimentally fragmented across all stages in 11 healthy, normal volunteers for two nights using auditory and mechanical stimuli. Primary outcomes included insulin sensitivity (S(I)), glucose effectiveness (S(G)), and insulin secretion, as determined by the intravenous glucose tolerance test. Secondary outcomes included measures of sympathovagal balance and serum levels of inflammatory markers, adipokines, and cortisol. Following two nights of sleep fragmentation, S(I) decreased from 5.02 to 3.76 (mU/L)(-1)min(-1) (P < .0001). S(G), which is the ability of glucose to mobilize itself independent of an insulin response, also decreased from 2.73 x 10(-2) min(-1) to 2.16 x 10(-2) min(-1) (P < .01). Sleep fragmentation led to an increase in morning cortisol levels and a shift in sympathovagal balance toward an increase in sympathetic nervous system activity. Markers of systemic inflammation and serum adipokines were unchanged with sleep fragmentation. Fragmentation of sleep across all stages is associated with a decrease in S(I) and S(G). Increases in sympathetic nervous system and adrenocortical activity likely mediate the adverse metabolic effects of poor sleep quality.